Gene expression profiles and protein–protein interaction network analysis in AIDS patients with HIV-associated encephalitis and dementia - Shityakov S (Dove Medical Press, 2015)
Sergey Shityakov,1 Thomas Dandekar,2 Carola Förster1 1Department of Anesthesia and Critical Care, 2Department of Bioinformatics, University of Würzburg, Würzburg, Germany Abstract: Central nervous system dysfunction is an important cause of morbidity and mortality in patients with human immunodeficiency virus type 1 (HIV-1) infection and acquired immunodeficiency virus syndrome (AIDS). Patients with AIDS are usually affected by HIV-associated encephalitis (HIVE) with viral replication limited to cells of monocyte origin. To examine the molecular mechanisms underlying HIVE-induced dementia, the GSE4755 Affymetrix data were obtained from the Gene Expression Omnibus database and the differentially expressed genes (DEGs) between the samples from AIDS patients with and without apparent features of HIVE-induced dementia were identified. In addition, protein–protein interaction networks were constructed by mapping DEGs into protein–protein interaction data to identify the pathways that these DEGs are involved in. The results revealed that the expression of 1,528 DEGs is mainly involved in the immune response, regulation of cell proliferation, cellular response to inflammation, signal transduction, and viral replication cycle. Heat-shock protein alpha, class A member 1 (HSP90AA1), and fibronectin 1 were detected as hub nodes with degree values >130. In conclusion, the results indicate that HSP90A and fibronectin 1 play important roles in HIVE pathogenesis.Keywords: microarray, human immunodeficiency virus, differentially expressed genes, protein–protein interaction network, gene ontology, encephalitis, dementia